ANALISIS INTERAKSI SIMBOLIS BATU AKIK BACAN DI KALANGAN MASYARAKAT SURABAYA) - Ningsih, Sri Wahyu; Hamim, Hamim; Soenarjanto, Bagus (representamen, 2018)
Research agate phenomenon as a symbol of this communication in the background agate background bythe icon as a symbol of social status differentiation in terms of both wealth and culture as well. Problemsof this research is the type of agate Bacan able to become a symbol of communication amongmasyarakat.Penelitian aims to determine the message symbols in agate frequently in associate withwealth and status sosial.penelitian using qualitative research The results of the study show that thesymbol is Non-verbal manifestation of a culture intent contained therein, as a symbol of social statusdifferentiator differentiator as well as cultural diversity. In relation to the communication titlephenomenon agate as a symbol of communication close relation to verbal communication which refers tospeech and non-verbal communication can be the symbol of the emblem as violence rocks / scale mohsand also fiber stone, whereas the results of research by the author intervenes after the interview is fromsome informants one of academics statement on responsible is in accordance with the theory of symbolicinteraction that communication tidah only through language but there are symbols that agreed upon inaddition to non-language and theories of social behavior by Albert Bandura that the individual isinfluenced by the social environment in if the surrounding environment fond agate then that individualwill have a tendency to follow the social life also has agate want.Keywords : Symbolic interaction, culture, agate Bacan.